Export Credit Agencies, Trade Finance and South East Asia - Stephens, Malcolm (IMF Working Papers; Working Paper ;, 1998)
This paper looks at the causes of the reduction in trade finance in South East Asian countries post-1997, with a particular focus on the role of export credit agencies. It concludes that while such agencies did not cause or prolong the problem, they did not contribute significantly to a solution. The paper also suggests some implications from events in South East Asia for both traditional debt-relief mechanisms and for the architecture of the international financial system.